Calculation of the pressure distribution between ski and snow - Heinrich, D.; Kaps, P.; Mössner, M.; Schretter, H.; Nachbauer, W. (Science and Skiing IV, 2009)
INTRODUCTION: The pressure distribution between ski and snow is an important factor for turns in Alpine skiing describing the interaction between ski and snow (Kaps, 2001; Federolf, 2005). The aim of the present study was to compute the pressure distribution during two consecutive turns using a validated Computer Simulation model. Additionally, the influence of edging and speed of the skier, as well as snow conditions should be quantified.